Rites of Ordination : Their History and Theology - Bradshaw, Paul F. (Book collections on Project MUSE., 2013)
"A Pueblo book."Includes index. Includes bibliographical references and index. Table of Contents: Historical and typological background -- Ministry in the earliest Christian communities -- Ministry and ordination in the third and fourth centuries -- Early ordination rites -- Ordination rites in the churches of the East -- Ordination rites in the medieval West -- The theology of ordination in the Middle Ages -- Orders and ministry in the churches of the Reformation -- The Roman Catholic Church from the Council of Trent to the present -- Other modern ordination rites.